A novel solution for heat conduction problems by extending scaled boundary finite element method. (April 2016) - Li, Fengzhi; Ren, Penghao
Highlights: The method for dealing with prescribed side-face uniform temperature problem is developed. A two-step method is presented for solving the SBFE inner temperature field. The results of the method combined SBFEM with PIM are not dependent on the time step size. The method for solving SBFE inner temperature field is effective and has satisfactory accuracy. Abstract: A technique to evaluate the temperature field is developed by extending the scaled boundary finite element method (SBFEM). Firstly, the method for the steady state problem with prescribed side-face uniform temperature is developed, so only the partial boundary of the problem domain is discretized. Secondly, the effect of the heat capacity on the element interior temperature field is taken into account for the transient heat conduction problem. Thirdly, an improved time domain precise integration method is developed for computing the boundary temperature of the SBFE, meanwhile, a finite-difference scheme is adopted to obtain the element interior temperature at different time. Finally, three examples are presented to illustrate feasibility and good accuracy of the proposed methods.